The Effect of Shuttle Run Training on VO2Max Physical Condition Results in Dojo Ziezoyuki Karate Academy Athletes - Kadek Yogi Parta Lesmana; I Ketut Semarayasa; I Gusti Lanang Agung Parwata; I Wayan Artanyasa; I Ketut Iwan Swadesi (Jurnal Pendidikan Jasmani, Olahraga dan Kesehatan Undiksha, 2024)
This research aims to provide an exercise that can increase the endurance of Dojo Ziezoyuki Karate Academy athletes. Because by providing good endurance training, an athlete will be able to apply techniques and tactics to the maximum, so that with excellent endurance abilities the opportunity to achieve achievements will be easier. This research is experimental research, where this research is used to determine whether there is an influence or effect on an object that has been studied. In this study, data collection was carried out using a multiple choice question type test using an initial test (pretest) and a final test (post-test). The population of this study were all karate athletes who actively trained at the ZIEZOYUKI KARATE ACADEMY Dojo, totaling 20 karateka. sample of 30 people with a sampling technique using total sampling. The instrument used in this research is the Multistage Fitness Test (MFT). In this research, data collection was carried out during the pre-test and post-test. The data that has been collected will be analyzed using Paired-test with the help of SPSS at a significance level of 5%. . The normality test was carried out using the IBM SPSS 20 software. The homogeneity test was carried out with the help of the IBM SPSS 20 software using the Levene's test with reference to the probability value or Sig. based on mean. The VO2 pretest results for men showed that the minimum value was 22.25, the maximum value was 40.13, the mean was 31.5625, the median was 31.1900, and the standard deviation was 5.80528. Meanwhile, the VO2 pretest results for women had a minimum value of 6.60, a maximum value of 31.19, a mean of 20.2075, a median of 23.3650, and a standard deviation of 8.25331. After carrying out the VO2 posttest, the maximum value increased to a minimum value of 28.95, a maximum value of 45.72, a mean of 37.7108, a median of 36.2200, and a standard deviation of 6.09969 for men, while for women the posttest VO2 result was a minimum value of 11.07 , maximum value 37.90, mean 23.0863, median 23.9250, and standard deviation 8.79715. It is proven that efforts to increase VO2 Max through shuttle run training have an influence on increasing VO2 Max Karateka Dojo ZIEZOYUKI KARATE ACADEMY in 2023, and have a big influence on performance when Karateka competes directly.